Pemanfaatan Sistem Informasi Geografis untuk Penapisan Nilai Konservasi Tinggi Skala Lanskap di Kabupaten Siak, Riau - M Sayidina Ali; Iing Nasihin; Dede Kosasih (Universitas Kuningan, 2025)
Non-forest estate (APL) is classified as a non-forestry cultivation area. Therefore, they have significant potential for conversion into cover and other uses for economic development. Furthermore, APL also offers potential for biodiversity and other functions related to ecosystem balance. Efforts to ensure ecosystem balance in APL include the identification of High Conservation Values ​​(HCVs). However, HCVs have been partially implemented in concession areas. Therefore, it is crucial to enforce HCVs at the landscape level or within specific juridictions. This study aims to identify and map areas with high/low probability of HCVs 1 to 4 in Siak Regency, Riau Province, and their threats. The research method used is a quantitative descriptive method, with HCV screening guidelines referring to High Conservation Value (HCV) Screening: Guidance for identifying and prioritizing action for HCVs as part of the jurisdictional and landscape approach initiated by HCV-RN. The study results indicate that HCV 1 – HCV 4 areas in Siak Regency, Riau Province, were identified in other use areas (APL) with area status as non-forestry cultivation areas, encompassing both high and low probabilities. Meanwhile, the threat ranking of HCV 1-HCV 4 consists of high – very high threats, with the form of threats in the form of land conversion for the expansion of BPPH HT in forest areas (HP, HPT, HPK) and the expansion of oil palm plantations in APL, forest and land fires, illegal logging, issuance of Tora permits, animal conflicts due to the reduction in area and quality of habitat, the entry of invasive species, canalization, and pollution of river, lake and swamp ecosystems. Keywords: Non-forest estate, High Conservation Value, Screening